2013
DOI: 10.1016/j.anr.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experiences of Nursing Home Residents in Korea

Abstract: The results of this study confirmed the positive and negative emotions that elderly people typically experience while in nursing homes. Nurses should educate the families of nursing home residents, so that the family can better respect elderly people's opinions and provide them with adequate support. Furthermore, nurses must not only provide reliable support, resources and serve as advocates, but they must also pay more attention to the environment of the nursing home to make it feel like home to the elderly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 17 publications
7
56
0
Order By: Relevance
“…One issue for older Iranian people when moving into an ACH is the considerable communication isolation they experience, especially from their family members. The isolation and separation from previous contacts have been confirmed in previous studies conducted in Western countries (Hauge & Kristin, ; Riedl et al., ) and in Southeast Asia (Chang, ; Tsai & Tsai, ). In participants with previously well‐established family networks, the social and communication isolation they experienced in transitioning to the ACH appeared to be far more distressing than for other resident participant.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…One issue for older Iranian people when moving into an ACH is the considerable communication isolation they experience, especially from their family members. The isolation and separation from previous contacts have been confirmed in previous studies conducted in Western countries (Hauge & Kristin, ; Riedl et al., ) and in Southeast Asia (Chang, ; Tsai & Tsai, ). In participants with previously well‐established family networks, the social and communication isolation they experienced in transitioning to the ACH appeared to be far more distressing than for other resident participant.…”
Section: Discussionsupporting
confidence: 72%
“…These psychosocial responses often relate to the older person's change of social roles, contacts and status, reduced autonomy, feeling of homelessness, and reduced opportunity to continue in domestic and other meaningful daily life activities (Porter & Clinton, 1992). While these transition effects are commonly reported in Western (Hauge & Kristin, 2008;Riedl et al, 2013) and Southeast Asian societies (Chang, 2013;Tsai & Tsai, 2008), there is almost no published research on the issue in Middle Eastern countries, despite a gradual increase in the number of people transitioning to an ACH in countries such as Iran (Sigaroudi, Nayeri, & Peyrovi, 2013).…”
mentioning
confidence: 99%
“…The phenomenology method is one of the methodologies used in qualitative research and is a method of choice for investigating what an experience means to a particular group of people. This method has been successfully applied in many nursing studies (Chang, ; Earle, ; Grossoehme, ; Tsai & Tsai, ). We used this phenomenology method for exploring the lived experiences and the subjective perception of the elderly enrolled in the ECDs in the CHSCs.…”
Section: Methodsmentioning
confidence: 99%
“…21,30 Additionally, many factors appear to contribute to the nutritional condition evidenced with aging. 31,32 Smoking, alcohol consumption, lifestyle (sedentary behavior, physical inactivity, poor diet), hormonal changes, and diseases can contribute to malnourishment. 31,33 The study showed that higher proportion of malnourished individuals was found among the smokers (26.2%).…”
Section: 27mentioning
confidence: 99%